Conjoint Couple Therapy with a Woman Survivor of Intimate Partner Violence: Strengths and Challenges - Roniyamol Roy; Mysore Narasimha Vranda; Aarti Jagannathan; Vasanthra Radhakrishnan Cicil; James Ranjith Prabhu (Indian Journal of Psychological Medicine, 2023)
Intimate Partner Violence (IPV) or Domestic Violence (DV) affects the mental health of women. Systemic family therapy has been found to help bring change in a couple's relationship and the cessation of violence in the relationship, provided both couples are motivated by the therapy to preserve the marital relationship. This article presents a case of offering brief tailor-made individual intervention as well as couple therapy for a woman with depression experiencing violence.